Aero-validation of CFD Methods for Turbine rear structures using experimental data - Nilsson, Mattias (My University, 2019)
Secondary flow effects in an axial turbine are highly complex and have a significant impact on the performance of an aircraft engine. Understanding the flow in the engine is essential to improve the design and increase engine efficiency. In order to increase understanding of the aerodynamics in a Turbine Rear Structure (TRS) tests are conducted at experimental facilities. The resulting test data provides valuable input in improving the prediction tools used in the design of the TRS. The aim of this study is to use computational fluid dynamics (CFD) simulations to increase the understanding of differences between prediction method results and experimental data. The CFD predictions are compared to test data from a turbine test facility capable of reproducing realistic engine conditions. The same operating conditions as in the test facility are used on the same geometry to produce the numerical results. Comparisons of blade loading, swirl angle and total pressure profiles are made for design and off-design conditions using different turbulence models. For some cases, a heat transfer investigation is also conducted. The results show how steady state simulations can be used to reproduce a close approximation of the experimental measurements for both design and off-design conditions.
Keywords: Transport; Hållbar utveckling; Strömningsmekanik och akustik; Transport; Sustainable Development; Fluid Mechanics and Acoustics